Readiness of Libraries in Building Knowledgeable Society - Atiqa Nur Latifa Hanum (Record and Library Journal, 2022)
Background of the study: Facing the challenges of society 5.0, Pontianak as the city in West Kalimantan has maneuvered by establishing several libraries and parks with reading facilities in the potential areas. Three of them are in the tourist area on the Kapuas riverbank. Communities living around libraries have vulnerability due to environmental, economic, and educational problems.